Microbial iron oxide respiration coupled to sulfide oxidation - Song-Can Chen; Xiao-Min Li; Nicola Battisti; Guoqing Guan; Maria A. Montoya; Jay Osvatic; Petra Pjevac; Shaul Pollak; Andreas Richter; Arno Schintlmeister; Wolfgang Wanek; Marc Mussmann; et al. (Nature, 2025)
Abstract Microorganisms have driven Earth’s sulfur cycle since the emergence of life 1–6 , yet the sulfur-cycling capacities of microorganisms and their integration with other element cycles remain incompletely understood. One such uncharacterized metabolism is the coupling of sulfide oxidation with iron( iii ) oxide reduction, a ubiquitous environmental process hitherto considered to be strictly abiotic 7,8 . Here we present a comprehensive genomic analysis of sulfur metabolism across prokaryotes, and reveal bacteria that are capable of oxidizing sulfide using extracellular solid phase iron( iii ). Based on a phylogenetic framework of over hundred genes involved in dissimilatory transformation of sulfur compounds, we recorded sulfur-cycling capacity in most bacterial and archaeal phyla. Metabolic reconstructions predicted co-occurrence of sulfur compound oxidation and iron( iii ) oxide respiration in diverse members of 37 prokaryotic phyla. Physiological and transcriptomic evidence demonstrated that a cultivated representative, Desulfurivibrio alkaliphilus , grows autotrophically by oxidizing dissolved sulfide or iron monosulfide (FeS) to sulfate with ferrihydrite as an extracellular iron( iii ) electron acceptor. The biological process outpaced the abiotic process at environmentally relevant sulfide concentrations. These findings expand the known diversity of sulfur-cycling microorganisms and unveil a biological mechanism that links sulfur and iron cycling in anoxic environments, thus highlighting the fundamental role of microorganisms in global element cycles.